The Impact Of Globalization On The Performance Of Commercial Banks In Nigeria: A Long –Run Equilibrium Analysis - Okanta, Sunday Ukeje; Ogbonna, Ben (Archives of Business Research, 2017)
The research examined the effects of globalization on the performance of Nigerian Commercial banks between 1986 and 2015. Specifically, the research accomplished this task using proxies such as foreign private investment policy, foreign trade policy and exchange rate policy to represent globalization, and using profits before taxes as a proxy for commercial banks’ performance. The research employed panel data econometrics in a pooled regression, utilizing autoregressive (dynamic) models in which time series observations were estimated. Tests of model adequacy and normality of residuals, including the test of heteroskedasticity were conducted. The t and F statistics, Durbin-Watson and Breusch-Godfrey tests for the overall significance of the estimated regression and serial autocorrelation first-order were also conducted. Variance decomposition test of the banks’ profits before taxes was carried out to establish (for the next 10-year period) the short-run equilibrium swings of the banks’ future performance shocks and the ability to recover from the shocks. The results of econometric regression analyses confirmed the following: The autoregressive models were adequate (i.e. they were stable); that is, the model variables and residuals were normally distributed and equally spread (homoscedasticity).There were no first-order serial autocorrelation, a confirmation of the overall significance and non-spuriosity of the findings of the research. In all, foreign private investment and exchange rates had positive and significant effects on the current profits before taxes of commercial banks in Nigeria. However, foreign trade policies had less positive and significant effects on bank performance in Nigeria in the past 30 years; and the 10-year period variance decomposition of the variables showed that the banks would face their own short-run shocks 100% in the first- year period and recover at zero percent in the same year. However, they would face 42.4% of such a shock and recover about 58% of it in the 10th year. The research recommended greater integration of banks in Nigeria to the global community for greater business earnings.